Answer:
The difference between two consecutive numbers in this sequence would be something like:
(2n + 1)^(2*k) - (2n)^(2k)
(or in the other order, but is essentially the same)
where n is an integer number.
Then:
2*n is an even number
2*n + 1 is an odd number.
(2n)^(2k) = 2*(2^(2k-1)*n^(2k)) this will be even for any natural number k.
(2n + 1)^(2k)
Let's suppose that k = 1.
Then we have:
(2n + 1)^(2) = (2n + 1)*(2n + 1) = (2n)^2 + 4n + 1 = 2*(2n^2 + 2n) + 1
If (2n^2 + 2n) is an integer (and it is) we can rename it as N
(2n + 1)^(2) = 2*N + 1
It is still odd.
Now if k = 2, we will have:
(2n + 1)^(2*2) = (2n + 1)^(4)
And using what we found above, we can rewrite this as:
(2*N + 1)^2
And we know that this will be odd.
Then we can already see that:
(2n + 1)^(2k) will be odd for any value of k (where k is a natural number)
Then:
(2n + 1)^(2k) - (2n)^(2k)
Is the difference between an odd number and an even number, and this will always be an odd number.